Jenny zero ebook - Dwonch, Dave (Jenny Zero (2021)., 2022)
Meet Jenny Zero, the hard partyin' daughter of Japan's most beloved superhero. After washing out as the military's top Kaiju-killer, Jenny lives the celebutante life with her hotel heiress bestie. But freakish creatures, secret societies, and her father's legacy now have her wondering if she can sober up‚Äîjust long enough to save the world! This volume collects Jenny Zero #1-#4, as well as a sketchbook section with creator commentary! ''Depraved and unhinged, Jenny can be best described as Paris Hilton meets Commando, and I, for one, am here for all of it.'' ‚ÄìGWW